2014
DOI: 10.1161/circ.130.suppl_2.18218
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 18218: In Vitro Characterization of Andexanet Alfa (PRT064445), a Specific fXa Inhibitor Antidote versus Aripazine (PER977), a Non-specific Reversal Agent

Abstract: New oral fXa inhibitors have been increasingly adopted for VTE or AF treatment in the outpatient setting instead of warfarin. Andexanet alfa (AnXa) is a modified, recombinant human fXa molecule developed as a specific antidote to reverse anticoagulant activity of fXa inhibitors during episodes of serious bleeding or before urgent surgery. PER977, a small molecule under development by Perosphere, Inc., is reported to reverse the effect of a broad range of anticoagulants (fXa and thrombin inhibitors, LMWH). In o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…Our results differed from the previous study conducted on LMWH, 15 in that we did not find a significant reversal of LMWH anticoagulation. One difference is in the methodology and administration of andexanet alfa, where our study was run in vitro , and the other study was performed in vivo in rats.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results differed from the previous study conducted on LMWH, 15 in that we did not find a significant reversal of LMWH anticoagulation. One difference is in the methodology and administration of andexanet alfa, where our study was run in vitro , and the other study was performed in vivo in rats.…”
Section: Discussioncontrasting
confidence: 99%
“…A case report from 2019 noted that a patient was unresponsive to UFH anticoagulation during surgery following an andexanet alfa reversal. 13,14 Previous research has also shown that recombinant factor Xa may be effective at reversing LMWH 15 and UFH. 16 Furthermore, it appears that andexanet alfa binds directly with UFH and LMWH and interestingly, binds to heparin-activated antithrombin.…”
Section: Introductionmentioning
confidence: 99%
“…No binding to FIIa and FXa, plasma proteins, or other drugs was found [75]. Lu et al suggested a possible increase in human platelet activation by ciraparantag using P-selectin expression induced by 10 µM adenosine diphosphate [76]. In this study, ciraparantag did not bind DOACs in vitro, which may depend on the assay.…”
Section: Ciraparantag (Per977)mentioning
confidence: 47%